PENGARUH PESAN DAKWAH USTAZ ABDUL SOMAD TERHADAP PEMAHAMAN KEAGAMAAN JAMAAH PENGAJIAN DI KOTA PEKANBARU - Dira Putri Deza; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was motivated by the presence of a phenomenal preacher until 2019, Ustaz Abdul Somad. Ustaz Abdul Somad, or who is usually better known as UAS, is very popular in all circles, be it parents, teenagers and even children with an interesting method of delivering da'wah and always makes people want to listen. In addition, the material of the da'wah message delivered by Ustaz Abdul Somad is the entire teachings of Islam in the Qur'an and the Sunnah of the Apostles. This study aims to analyze the influence of Ustaz Abdul Somad's preaching message on the religious understanding of recitation worshipers in Pekanbaru City and to determine the effect of Ustaz Abdul Somad's preaching message on religious understanding of recitation worshipers in Pekanbaru. The theory used in this research is stimulus response theory. This study examines the message of preaching as independent (X) and religious understanding as the dependent variable (Y).               The research method used in this research is quantitative descriptive. The research method used in this research is quantitative descriptive. Data collection using questionnaires, observation and documentation. The population in this study are people who have attended Ustaz Abdul Somad's study in Pekanbaru City whose exact numbers are unknown. The sample in this study amounted to 166 respondents obtained based on the formula unknown population with random sampling withdrawal techniques. Data measurement using a Likert scale. The data analysis technique used in this study is simple linear regression.               The results showed the value of sig. 0,000 obtained based on measurements through the SPSS Version 24.0 program is smaller than the 0.05 probability, thus it can be concluded that the independent variable (Da'wah Message) significantly influences the dependent variable (Religious Understanding) or Ha is accepted and H0 is rejected. Message Da'wah Ustaz Abdul Somad has a proportion of influence of 41.2% on the Religious Understanding of the Recitation Congregation in Pekanbaru City.